Modeling and simulation of hybrid system for electricity generation in rural area (microturbine, biodiesel, solar photovoltaic and battery/MTBDSPB) - Kareem, Hayder Jasim (2015)
Design and implementation of an efficient yet techno-economic hybrid generator for off-grid electric supply is challenging. The cost-effectiveness and convenience offered by off-grid rural electrification system that integrates various renewable energy sources (RESs) became inevitable for areas where grid connection is neither available nor feasible. A hybrid combination of renewable energy technologies (RETs) is proven to be a suitable alternative over expensive grid extension for remote areas worldwide. This study proposes a hybrid model for electricity generation by assimilating renewable resources such as solar photovoltaic (SPV) and microturbine (MT) together with biodiesel generator (BDG) to fulfill the electricity demand of an off-grid remote village Perkampungan Orang Asli Sungai Jahai, Perak in Malaysia. The suitable renewable energy resources for the proposed hybrid system are identified to determine the daily load profile and cost-effectiveness that can be afforded by the villagers. The model is further simulated using HOMER software to evaluate the optimum performance of the hybrid system where the abovementioned village is taken for case study. The simulated results are analyzed, compared, and understood. The load demand pattern of the village over different months is accurately computed. The sizes of MT, SPV, and BD systems are optimized to achieve the minimized cost of energy (COE) generation. It is demonstrated that the use of decentralized RETs at an off-grid location is indeed the best alternative towards grid extension. Furthermore, HOMER data reveals the sustainability, techno-economic viability, and environmental friendliness of the proposed model based energy solution. The sensitivity analysis by combining MT, SPV, and BD is found to achieve the COE generation of $0.309 kWh which is much more than the present heavily subsidized electricity tariff of rural area in Malaysia (3.3 cent/kWh). Although, the COE obtained from the proposed hybrid system is nearly 10 times higher but it is significantly lower than a diesel generator alone ($0.70/kWh). The admirable features of the results suggest that the proposed hybrid generator may be beneficial for off-grid electricity generation and supply in remote rural regions.